FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN DYSMENORRHEA PADA SANTRI PUTRI DI PESANTREN MA’HAD IZZATUNA PUTRI KOTA PALEMBANG - Haziza Hasada; Fika Minata Wathan; Rizki Amalia; Siti Aisyah Hamid (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Dysmenorrhea is one of the problems in adolescent reproductive health. The factors that influence dysmenorrhea are the factors that cause dysmenorrhea including age of menarche, stress and fast food consumption behavior (Sulfa Dianal, Hedy Herdiana2, 2023), nutritional status, menstrual patterns and family history (Hayati et al., 2020), knowledge and nutritional status (Septi et al, 2021), duration of menstruation (Mouliza, 2020), physical activity (Sugiyanto & Luli, 2020), sleep quality (Cahyaningsih et al., 2021) and cigarette smoke (Akbar et al., 2023). The purpose of the study was to determine the relationship between duration of menstruation, physical activity and diet (fast food) with dysmenorrhea. The research method used quantitative with an analytical survey design through a Cross Sectional approach. The population. in the study were all female senior high school students at the Ma'had Izzatuna Putri Islamic Boarding School, totaling 47 people. The sample determination was taken using the total sampling technique, the research sample were all female senior high school students at the Ma'had Izzatuna Putri Islamic Boarding School. The results of the chi-square test showed that there was a relationship between the duration of menstruation and dysmenorrhea in female students with a p-value of 0.040, there was no relationship between physical activity and dysmenorrhea with a p-value of 0.137, and there was a relationship between diet (fast food) and dysmenorrhea with a p-value of 0.025. Based on the results of the study, it is recommended to schools in order that can provide information related to adolescent reproductive health, especially about dysmenorrhea.